An investigation of heat treatment effect on the mechanical properties of the aluminium alloy - Muhammad Aizuddin Fikry, Ruslan; Radhiyah, Abd Aziz (Institution of Engineering and Technology, 2022)
The alloy ADC12 also is used to make die-casting components. Heat treatment is used to improve the mechanical properties and can gave crack after treatment cause improper cooling rate. When the cooling rate is too slow, undesired grain boundary precipitation occurs, and when the cooling rate is too high, distortion will occur. There have several problems statement that can cause of cracking and fracture during produce the part which are the material has high hardness and brittle. Improper heating to the austenitizing temperature may result in thermally generated stress, resulting in the opening of a flaw into a fracture. Solution treatment and ageing process was applied to ADC12. The UTS of ADC12 drop after solution treatment from 320.60 MPa to 12.43 MPa. The UTS significant increase after apply ageing process to solution treated ADC12 with temperature 135°C and it reach the highest elongation length which 14% at 10 hours holding time. The elongation decreases after applied ageing process at 240°C with different holding time. It shows that, temperature and holding times are the factor effect changes of mechanical properties of ADC12. From the result, it showed that the mechanical properties of ADC12 are reliably achieved by following solution treatment: 8 hours at 450°C and quenching into the water. Then applied ageing process in 10 hours at 135 °C and slow cooling in the oven. Thus, it showed that solution treatment could reduce the UTS and hardness of ADC12, but enhance the elongation. With the aging treatment. It could increase the hardness of the solution treated ADC12.